Accounting Education: The Historical Development of Auditing From Ancient Origins to Modern Standards - Muslim Muslim; Muh. Reza Ramdani (Vifada Journal of Education, 2024)
This study aims to explore the historical development of auditing, tracing its evolution from ancient origins to modern standards, and to analyze the socio-economic, technological, and regulatory factors that have shaped the profession over time. Employing a qualitative literature review methodology, the research design involves thematic analysis of scholarly articles, books, and reports to identify key themes and concepts relevant to the research topic. The findings highlight the significance of ancient auditing practices rooted in the need for fairness, accountability, and transparency in economic transactions and the transition to modern auditing standards driven by factors such as the rise of joint-stock companies, technological innovations, and regulatory reforms. The discussion emphasizes the implications of these findings for auditing practice, regulation, and governance, underscoring the importance of continuous innovation, adaptation, and collaboration to address emerging challenges and ensure the integrity and relevance of auditing in the 21st century. The study's implications extend to academic scholarship, professional practice, and regulatory policy-making, emphasizing further research on technological advancements, regulatory reforms, and cultural influences on audit quality, auditor behavior, and financial reporting integrity.